Fractional photo-current dependence of graphene quantum dots prepared from carbon nanotubes - Kundu, Sumana; Ghosh, Sujoy; Fralaide, Michael; Narayanan, T. N.; Pillai, Vijayamohanan K.; Talapatra, Saikat (Physical Chemistry Chemical Physics, 2015)
We report on the photo-conductivity studies of chemically synthesized graphene quantum dots (GQDs) of average size 12 nm obtained by the oxidative acid treatment of MWCNTs. The dependence of photocurrent I-ph (I-ph = I-ill - I-dark) on the laser intensity P under a wide range of laser intensities (5 mW <= P <= 60 mW) shows a fractional power dependence of I-ph on light intensity. The temperature dependence (300 K < T < 50 K) of I-ph observed in thin films of these GQDs indicates that in the higher temperature region (T > similar to 100 K), as the temperature increases, the number of thermally generated carriers increase resulting in increased I-ph. At sufficiently low temperatures (T <= 100 K), a constant I-ph is observed, indicating a constant photocarrier density. Such a behavior is typically observed in many photoactive disordered semiconductors, which are often used in a variety of applications. We believe that the investigations presented here will enhance our understanding of the photocurrent generation phenomenon in chemically obtained GQDs.

Synthesis of N, F and S co-doped graphene quantum dots - Kundu, Sumana; Yadav, Ram Manohar; Narayanan, T. N.; Shelke, Manjusha V.; Vajtai, Robert; Ajayan, Pulickel M.; Pillai, Vijayamohanan K. (Nanoscale, 2015)
Graphene quantum dots (GQDs) are a promising category of materials with remarkable size dependent properties like tunable bandgap and photoluminescence along with the possibility of effective chemical functionalization. Doping of GQDs with heteroatoms is an interesting way of regulating their properties. Herein, we report a facile and scalable one-step synthesis of luminescent GQDs, substitutionally co-doped with N, F and S, of similar to 2 nm average size by a microwave treatment of multi-walled carbon nanotubes in a customized ionic liquid medium. The use of an ionic liquid coupled with the use of a microwave technique enables not only an ultrafast process for the synthesis of co-doped GQDs, but also provides excellent photoluminescence quantum yield (70%), perhaps due to the interaction of defect clusters and dopants.